THE CATHARTIC FUNCTION OF SEBASTIÃO SALGADO’S PHOTOGRAPH - Marchezan, Luiz Gonzaga (Laboratório Editorial FCL-UNESP, 2012)
This article compares the different photographic acts of Henri Cartier-Bresson and Sebastião Salgado.